Implementasi Model Discovery Learning Berbantuan Powtoon untuk Meningkatkan Minat Belajar IPAS Kelas VI Sekolah Dasar - Ansya, Yusron Abda'u; Salsabilla, Tania (ISLAMIKA, 2025)
This study aims to describe the implementation of the Powtoon-assisted discovery learning model in increasing student interest in learning Ilmu Pengetahuan Alam (IPAS) in sixth-grade elementary school. This study uses a qualitative approach with a descriptive method to observe and analyze the phenomena that occur during the implementation of the learning model. The subjects of this research are sixth-grade students at UPT SD Muhammadiyah 29 Sunggal, totaling 56 students and 2 teachers at the school.. The research results show that the use of Powtoon as a learning medium in the discovery learning model successfully increased students' interest in learning. Students became more active in participating in class discussions, increased their curiosity, and were more enthusiastic about the IPAS learning material. Student interaction with Powtoon media and the learning process also showed significant changes, where students engaged more in discussions and collaborated more in completing tasks. However, there are several obstacles, such as technical issues related to devices and internet connectivity that affect the smoothness of the learning process. The conclusion of this study is that the application of the Powtoon-assisted discovery learning model can enhance students' interest in learning IPAS, although attention needs to be given to technical obstacles and the readiness of infrastructure in schools.